Resistance to oxacillin, erythromycin and gentamycin in coagulase negative Staphylococcus strains isolated from blood cultures - Maribel Castellano González; Armindo José Perozo-Mena; Raquel Devis Soto (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2016)
Resistance to antimicrobials in Gram-positive bacteria such as coagulase negative Staphylococcus is an emerging global threat. The purpose of this research was to identify the genes for resistance to oxacillin (mecA), erythromycin (erm and msrA), and gentamicin aac(6´)/aph(2´´), in Staphylococcus coagulase negative strains isolated from blood cultures from patients attended at the University Hospital in Maracaibo. Phenotypic detection was performed using automated methods. Polymerase chain reaction was used for the detection of antimicrobial resistance genes. Be studied 34 strains whose distribution by species was: S. haemolyticus (38.23%), S. epidermidis (29.42%), S. hominis (26.47%), S. xylosus and S. capitis (5.88% each one). All strains were resistant to oxacillin. Gentamicin resistance varied between 38.46% and 100%; while the erythromycin resistance ranged between 77.78% and 100%. The analyses showed the presence of genes mecA (100%), ermA (35.2%), ermC (41.17%), msrA (17.64%), and aac(6´)/aph (2´´) (61,76%). In conclusion, is found a high frequency of genes for resistance to these antibiotics and the intensive care unit was the health service where the highest percentage of isolated strains carriers of these genes.